Analysis of determinants of tax avoidance in property and real estate companies: the role of capital intensity, corporate governance, transfer pricing and company size as moderating variables - Rani Nurul Hidayati; Sulistyowati Sulistyowati (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2025)
This study aims to examine the effect of Capital Intensity, Corporate Governance and Transfer Pricing on Tax Avoidance with Company Size as Moderation. This research was conducted at property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. This research uses quantitative research with an associative approach, measured using panel data regression analysis techniques and moderated regression analysis (MRA) using the help of Eviews software version 12. The population in this study were property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023, totaling 92 companies. Sampling using purposive sampling technique and obtained a sample of 7 companies, so that the total observations in this study were 35 observations. The data used in this study is secondary data. The data collection technique uses the documentation method through the IDX official website, namely www.idx.co.id and the Company's official website. Hypothesis testing in this study used the t test. The results of the study prove that (1) Capital Intensity have no effect on Tax Avoidance, (2)Corporate Governance and Transfer Pricing has a significant positive effect on Tax Avoidance, (3) Company Size is able to moderate and strengthen the effect of Corporate Governance and Transfer Pricing on Tax Avoidance, (4) Company Size is unable to moderate the effect of Capital Intensity on Tax Avoidance.